Socialization of the Importance of the Agency's SPT Strategy and Development UMKM Strategy in Parungpanjang District - Hidayatul Mu `Arifin; Siti Ratna Sari Dewi; Iin Rosini (Ridwan Institute, 2021)
The purpose of this research is to provide an understanding of the making of the Agency's Annual SPT and the development strategy of MSME-IKM and to find out what obstacles are faced during the MSME-IKM Kec Forum. Parungpanjang at the time of making the annual corporate tax return. To achieve this goal, training activities for the preparation of the Agency's Annual SPT were carried out in UMKM-IKM Kec. Parungpanjang. The method used in this research is through training and coaching activities. The data collection method used in this study is a quantitative and descriptive method, namely by reviewing, researching, and providing training and guidance to companies in recording transactions and making annual and periodic tax returns. Thus making the company more effective and efficient in dealing with financial reporting and tax reporting issues. This bookkeeping and recording becomes a very crucial thing because what is recorded or recorded will be the basis for every taxpayer to calculate the amount of tax owed. From the results of this study, financial transactions have not been properly recorded into financial statements, although simple because there are many obstacles in making the annual corporate tax return, one of the factors is that human resources or managers do not understand a